Red to white polymer light-emitting diode (PLED) based on Eu3+–Zn2+–Gd3+-containing metallopolymer. Issue 19 (4th May 2017) - Liu, Lin; Li, Hongyan; Su, Peiyang; Zhang, Zhao; Fu, Guorui; Li, Baoning; Lü, Xingqiang
Abstract : With color-tunable Eu 3+ –Zn 2+ –Gd 3+ -containing metallopolymerPoly(2- co -MMA- co -8) as the emitting layer, bright color-purity red-light PLED to first-example Ln 3+ -containing-metallopolymer-based WPLED were realized. Abstract : Through terpolymerization of the red-light complex monomer [Eu(tta)3 (4-vp-2, 2′bpy)] (2 ; Htta = 2-thenoyltrifluoroacetone; 4-vp-2, 2′-bpy = 2-(pyridin-2-yl)-5-(4-vinylphenyl)pyridine), blue-green-light complex monomer [Zn(L)(4-vinyl-Py)Gd(NO3 )3 ] (8 ; Salen-type H2 L = N, N ′-bis(3-methoxy-salicylidene)phenylene-1, 2-diamine; 4-vinyl-Py = 4-vinyl-pyridine) with MMA (methyl methacrylate), the obtained Eu 3+ –Zn 2+ –Gd 3+ -containing metallopolymerPoly(2- co -MMA- co -8) (120 : 1[2 /8 = 2 : 1 or 1 : 2]) exhibits stoichiometry-dependent color-tuning photoluminescence due to effective Zn 2+ –Gd 3+ –Salen to Eu 3+ energy transfer. Moreover, using them as the corresponding emitting layers, a high color-purity red-light polymer light-emitting diode (PLED) with a luminous efficiency of 0.037 lm W −1 and first-example Ln 3+ -containing-metallopolymer-based WPLED with an eternal quantum yield of 0.003% is realized.